Liquid biopsy challenge and hope in colorectal cancer. (3rd April 2019) - Burz, Claudia; Rosca, Andreea; Pop, Vlad-Vasile; Buiga, Rares; Aldea, Cornel; Samasca, Gabriel; Silaghi, Ciprian; Sur, Daniel; Lupan, Iulia; Pricopie, Andreea
ABSTRACT: Introduction : Colorectal cancer is an important global health burden marked by a high mortality rate. Medical attention is drawn more often by the new targeted therapies, but also by the concept of liquid biopsy. Tumor's genetic profile is the major indicator of the response to targeted therapies and the risk for metastatic relapse. Therefore, analysis of tumor-linked genetic alterations holds a great importance, both for diagnostic and prognostic purposes. Areas covered : The present paper highlights the molecular basis of the liquid biopsy concept and its major clinical applications in colorectal cancer. This consists in circulating tumor cells (CTC) and cell-free tumor DNA (cfDNA) and is described in manuscripts as an alternative to tissue samples, providing more information about tumor heterogeneity and tumor evolution in dynamic. Expert opinion : Liquid biopsy is an innovative, minimally invasive method which enables real-time monitoring of tumor's genetic heterogeneity, being an important step towards personalized medicine. However, despite the large number of detection methods available, it is necessary to standardize them regarding the blood collection processing and sample storage, analysis in order to be implemented in clinical guidelines.